Development of Calligraphy Learning Media on Calligraphy Font Types in Higher Education - Dangkua, Suleman; Hasdiana, Hasdiana (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Learning media is one of the supporting components in the learning process. In the process of learning fine arts, especially in calligraphy courses, recognizing calligraphy letters is one of the topics studied. This course instructs students on how to transform calligraphy letters into two-dimensional works of art. In order for the learning process to run effectively, learning media are needed that are valid and practical and can be used as a tool to achieve learning objectives optimally. The purpose of this study was to evaluate and describe the feasibility of calligraphy learning media specifically designed for letter recognition material. The research method used is the R&D research and development method with the 4D approach. This research was conducted at the Bachelor of Fine Arts Education Study Program, Gorontalo State University. The findings from the validation of learning media by several validators showed values that serve as a reference for the validity and feasibility of the media. The values obtained include 85.62% from a material expert validator, indicating very feasible criteria; 81.40% from a media expert validator, also indicating very feasible criteria; and 72.79% from a calligrapher, which indicates feasible criteria. The use of student response questionnaires also affects the level of validity of learning media with a value of 77.66% for attractive criteria. As a whole, it proves that calligraphy learning media for recognizing calligraphy types is very feasible to develop.